2014
DOI: 10.1093/trstmh/trt116
|View full text |Cite
|
Sign up to set email alerts
|

Provider-initiated HIV testing and counselling for TB in low HIV prevalence settings: is it worthwhile?

Abstract: Background:We assessed the HIV-positive yield of offering provider-initiated HIV testing and counselling (PITC) for TB and the costs, in Madagascar, which has a low HIV prevalence and a high TB burden. Methods:A cross-sectional study of routinely collected records from January 2010 to June 2011.Results: A total of 37 596 TB patients were registered in 205 TB centres. HIV testing was available in 95 (46%) of centres where 7524 (40%) of those offered testing accepted it. Only 35 (0.5%) individuals were found HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…However, in Sudan, HIV testing and counselling is offered routinely to TB patients but not to suspected TB patients. The national policy dictates that HIV testing should be provided to TB patients; a policy evident in many countries with low HIV burden due to resources implications [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, in Sudan, HIV testing and counselling is offered routinely to TB patients but not to suspected TB patients. The national policy dictates that HIV testing should be provided to TB patients; a policy evident in many countries with low HIV burden due to resources implications [8].…”
Section: Introductionmentioning
confidence: 99%
“…PITC among diagnosed TB patients has become a standard practice in most national TB control programs in the last decade. However, PITC in patients with presumptive TB is not widely implemented globally, especially in low HIV burden countries, due to resource implications [8]. In the high HIV-burden countries of sub-Saharan Africa, studies have found that HIV-prevalence rates in presumptive TB patients are as high as those in diagnosed TB patients, with most of the HIV-positive patients being eligible for antiretroviral therapy (ART) and cotrimoxazole preventive therapy [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The national policy dictates that HIV testing should be provided to TB patients; a policy evident in many countries with low HIV burden due to resources implications [11].…”
Section: Introductionmentioning
confidence: 99%